MENUJU TEORI AKUNTANSI SYARIAH BARU - Aji Dedi Mulawarman; Iwan Triyuwono; Gugus Irianto; Unti Ludigdo (Jurnal Ekonomi & Keuangan Islam, 2011)
The purpose of this article is to develop shariate accounting theory called the New Islamic Accounting Theory (NIAT), constructed from simultaneous universalities of Islamic soul (Tauhid) and localities of Indonesian uniqueness (Moslem business activity). This methodology used is Extended Integrated Islamic Hyperstructuralism (EXIST)-revisited, based on purification (tazkiyah) that would take synergy of empirical and normative values. The result is, first, normative accounting values have Tauhid values. Second, the values from Indonesian Moslem is about unified tradition works (ma’isyah) to realize livelihood (rizq) and discover wealth (maal) that should be blessing of God (barakah). Third, synergy consequences from normative-empirical values compose the structure of shariate accounting theory that have unique accounting objectives and technological forms of shariate financial statements.